Intercultural Socialization through New Opportunities, Clil Technology in Inclusive Education (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article describes the achievement of intercultural adaptation through the study of foreign languages in the era of globalization, personal and professional development, and teaching foreign languages using modern technologies in inclusive education.